Validation of the ComCare index for rater-based assessment of medical communication and interpersonal skills. Issue 4 (April 2022) - Gärtner, Julia; Bußenius, Lisa; Schick, Kristina; Prediger, Sarah; Kadmon, Martina; Berberat, Pascal O.; Harendza, Sigrid
Highlights: The ComCareR is a valid scale to assess communication and interpersonal skills. It allows for quick rating in exam-like situations of physician-patient encounters. It can be used to provide the observer perspective in 360° assessments. Abstract: Objectives: To develop and validate a short instrument to assess undergraduate medical students' communication and interpersonal skills in videographed history taking situations with simulated patients. Methods: Sixty-seven undergraduate medical students participating in an assessment including videographed physician-patient encounters for history taking with five simulated patients were included in this study. The last video of each participant's consultation hour was rated by two independent assessors with the eight-item ComCare index for assessment of communication and interpersonal skills newly designed for the external rater perspective (ComCareR). We compared the sum scores of the ComCareR with ratings of the same videos with the Kalamazoo Communication Skills Assessment Form from an observational perspective (KCSAFd-video) and the Global Rating scale (GR), which also measure communication and interpersonal skills. Results: The ComCareR showed an excellent interrater reliability (ICC = .85). We found a small but significant correlation with the KCSAFd-video Interpersonal Competence (ρ = .34, 95% CI [.10, .54]) and a high positive correlation with the GR (ρ = .59, 95% CI [.40, .73]). Conclusions: The ComCareR is a valid and brief index for holistic assessment of communication and interpersonal skills in physician-patient encounters. Practice implications: The ComCareR can be used for quick rater-based assessment of physicians' communication and interpersonal skills.